Vliv hypodermatózy skotu na vybrané zdravotni ukazatele mléka u prvotelek - Ríha, J; Renda, V; Minár, J (Veterinarni medicina, 1979)
The effect of the last developmental phase of the warble fly (Hypoderma bovis de Greer) larvas was studied as exerted on some health indices of milk in 20 experimental (treated) and 18 control (untreated) first-calvers of the Pinzgau breed at two localities of an area affected by bovine hypodermosis in the period from May to June, 1975. The preparation Hypocid, at a dose of 15 ml per 100 kg of body weight, was applied externally in the lumbosacral region to the experimental animals in November, 1974. Throughout the experimental period (61 days) the milk was repeatedly examined bacteriologically and cytologically, the content of chlorides and the milk electric conductivity were determined. In none of the followed health indices of milk were significant differences in the values obtained from experimental and control first-calvers proved statistically.
Keywords: mléko; Lumbosacral Region; Insecticides; skot; hypodermyiáza; nemoci skotu; ženské pohlaví; zvířata; Hypodermyiasis; aplikace lokální; Cattle; Milk; insekticidy; Cattle Diseases; lumbosakrální krajina; Female; Diptera; Administration, Topical; Animals